Modelagem numérica e análise experimental do monitoramento da integridade estrutural de sistemas mecânicos baseado em impedância eletromecânica - Freitas, Fernanda Beatriz Aires de (2025)
The electromechanical impedance-based structural health monitoring technique (ISHM) has proven effective in detecting faults in various engineering structures. However, understanding its behavior is essential for optimizing its application. For this reason, a finite element model was developed in this work using ANSYS® software to represent the results obtained by the ISHM technique. With an accurate representation of this technique, it is possible to select the ideal piezoelectric transducer by appropriately defining its type, position, and size for coupling to the monitored structure. This approach not only contributes to reducing experimental costs but also enhances the effectiveness of damage identification. In addition to the proposed model, a sensitivity analysis is presented to identify the most influential parameters. Different adhesive layer thicknesses were also evaluated, comparing experimental and numerical results under healthy and damaged conditions. The results indicate that, despite variations in impedance signatures, there is a consistent trend between simulation and experiment, confirmed by the damage indices, which also follow the same trend. This approach enhances the application of the ISHM technique by providing a better understanding of its behavior, enabling a more precise implementation.